Researching contemporary wellness cultures - Smith, Naomi; Southerton, Clare; Clark, Marianne (Emerald Publishing Limited, 2024)
Wellness has become a mainstream concept, yet we have limited sociological understanding of how wellness functions in contemporary Western culture. Researching Contemporary Wellness Cultures is the first collection to bring together scholars examining wellness practices within various sociological sub-disciplines across and in related fields including anthropology, cultural studies, and internet studies. Investigating the growing field of wellness practices and practitioners, in order to understand the role of wellness practice in negotiations of the Western medical system. Researching Contemporary Wellness Cultures explores the various ways and spaces in which wellness is constructed, produced, circulated and contested, with contributing authors exploring everything from the intersections of wellness movements and far-right conspiracy spaces to the competing discourses at work in popular "What I Eat in a Day" videos on YouTube.
Keywords: Health promotion -- Sociological aspects.; Health behavior -- Sociological aspects.; Health attitudes -- Sociological aspects.; Well-being -- Sociological aspects.; Social Science -- Disease & Health Issues.; Health, Relationships and Personal development.; Health, illness and addiction: social aspects.; elektronické knihy; electronic books